Mulher, trabalho e saúde mental: as histórias de vida das trabalhadoras do município de Sobral como uma ponte entre o individual e o social - Melo, Carolina Silveira Leitão (2023)
This study seeks to understand how the relationship between being a woman and work contexts affects the mental health of workers. Careful analysis of these elements not only contributes to a more comprehensive understanding of the challenges faced by women, but also sheds light on possible strategies and policies that can be implemented to promote a more inclusive and equitable social structure. The social model of patriarchy has for years influenced how women act and live, generating challenges such as the sexual division of labor, the nuances of double or triple shifts, gender discrimination, the feminization of poverty, limiting their opportunities and bringing effects to their psychological health. Recognizing the intersectionality of the term woman and understanding work in its productive and reproductive forms, the main objective of this study is to understand the relationship between women, work and mental health based on the life stories of workers in the municipality of Sobral. To meet the proposal, qualitative research was carried out. The biographical life history method was defined for this objective as a way of giving voice to these workers, prioritizing their perceptions over the intertwining of defined categories of analysis in the light of their own narratives. The target audience is working women from the municipality of Sobral who sought care at the UFC-Sobral Applied Psychology Service (SPA), from August 2022 to June 2023, with work-related demands. To carry out the analysis of the data produced, Bardin's content analysis was used. We can infer that there is psychological suffering in being a woman in work contexts. The changes in the mental health of women in this social mold in which they are inserted leads them to exhaustion, overload, and impoverishment. The sexual division of labor, the precariousness of both productive and reproductive work and the absence of a social support network, which can alleviate the accumulation of activities, emerge as factors that affect the mental health of female workers. Based on the development of the research and data analysis, a publishing product was created, in this case an ebook, to be published virtually, bringing the life story narratives of the women participating in the research, with the purpose of elucidating possibilities for interventions of mental health care for working women.